Faktor Risiko Kejadian Demam Tifoid Di Rumah Sakit Tingkat II Pelamonia Makassar (Window of Public Health Journal, 2025)
Typhoid fever is a life-threatening infection caused by the bacterium Salmonella Typhi. This infection is usually spread through contaminated food or water. Typhoid fever remains a significant health issue worldwide, particularly in developing countries. In Indonesia, the incidence of typhoid fever remains high, ranking third among countries worldwide. This disease is present throughout the year and tends to increase in frequency. This study aims to determine the risk factors for typhoid fever at Pelamonia Class II Hospital, Makassar. The type of research used is a quantitative study with a case-control approach. The study population consisted of 113 respondents. The sample calculation employed the Lemeshow formula, yielding a sample size of 76 individuals with sample criteria of 38 cases and 38 controls. The instrument used was a questionnaire. Data analysis used the Odds Ratio (OR) test. The analyzed data are presented in tabular form and then explained in narrative form. The results of the study showed that gender OR value = 1.894, lower limit = 0.761 and upper limit = 4.716, personal hygiene OR value = 3.698 lower limit = 1.433 and upper limit = 9.541, eating habits outside the home OR value = 4.208 lower limit = 1.607 and upper limit = 11.014, and knowledge OR value = 2.949 lower limit = 1.159 and upper limit = 7.503 are risk factors for typhoid fever at Pelamonia Class II Hospital Makassar. The conclusion of this study shows that gender, personal hygiene, eating habits outside the home, and knowledge are risk factors for typhoid fever. It is hoped that the community will maintain personal hygiene and reduce eating habits outside the home to minimize the risk of exposure to typhoid fever and increase their knowledge, especially about preventing the disease, in order to avoid contracting it.